Antibacterial effect of cinnamon essential oil (Cinnamon cassia) in different concentration towards Streptococcus sanguis - Hajanajumudin, Hanizul; Satari, Mieke Hemiawati; Setiawan, Ame Suciati (Universitas Padjadjaran, 2010)
Introduction: Streptococcus sanguis is a type of normal bacteria found in the oral cavity, particularly in plaque on tooth surfaces and can also be found in saliva, buccal mucosa, tongue and gingival sulcus. At present, the usage of herbal remedy for reducing plaque in oral cavity has been implemented widely and one of the herbal remedy used is cinnamon essential oil. The purpose of this study is to prove that there are differences in the antibacterial activity of cinnamon essential oil with different concentrations against Streptococcus sanguis. Methods: The study was performed using laboratory experiments, in which the sensitivity of the Streptococcus sanguis bacteria from the saliva of 10 KPBI batch 2006 dental students were tested in vitro against cinnamon essential oil by using Kirby-Bauer method. Results: The study shows that the cinnamon essential oil has different antibacterial abilities in inhibiting the growth of Streptococcus sanguis in different concentrations. This is due to the element cinnamaldehyde and eugenol that they posses as their main constituent. There is a significant difference between the antibacterial effects of Cinnamon cassia essential oil in different concentrations towards Streptococcus sanguis. Conclusion: Cinnamaldehyde and eugenol has been proved to have antibacterial effect towards wide variety of bacteria including Streptococcus sanguis.